Silicon-based compacting agent and preparation method and application thereof
By modifying the silica fume and using it in combination with nanosilicon dioxide, fly ash and polymers, the problem of the prone to agglomeration of SiO2 particles in cement stone is solved, and the compactness and uniformity of cement stone is significantly improved.
Patent Information
- Application Number
- CN202211531540.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-01
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2042-12-01
AI Technical Summary
The existing silicon fume SiO2 particles are prone to agglomeration in cement stone, resulting in poor compactness of cement stone.
The silicone fume is modified by silicone compounds containing silicon oxygen groups, increasing the silanol groups, weakening the polarity between micro-nano particles, improving the dispersion of silicone fume, and combining nanosilica, fly ash and polymers to exert the filling effect and pozzolano effect.
It significantly improves the compactness and uniformity of cement stone, refines the pore structure, enhances the polymerization of hydrated calcium silicate gel, and improves the mechanical strength and durability of cement stone.
Smart Images

Figure BDA0003976275450000061 
Figure BDA0003976275450000071 
Figure BDA0003976275450000081
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of concrete materials, and in particular to a silicon-based compacting agent and a preparation method and application thereof. Background Art
[0002] Cement paste densifier has the function of improving the density of cement paste. It is mainly used in the field of bridges. It has the characteristics of refining pore size, improving the polymerization degree of hydrated calcium silicate gel, and reducing capillary water and interlayer water slip. Using silica fume as a densifier to mix into cement paste is low-cost and suitable for engineering applications, with good densification effect. However, the large specific surface area of silica fume and the high surface energy of SiO2 particles make silica fume SiO2 particles mostly exist in the form of agglomerates, which significantly reduces the effect of silica fume on densifying modified cement paste.
[0003] Therefore, a silicon-based compacting agent with better performance is needed to reduce the agglomeration of SiO2 particles and further improve the density of cement paste. Summary of the invention
[0004] The object of the present invention is to provide a silicon-based compacting agent to solve the technical problem that the existing compacting agent has poor compactness of cement paste due to agglomeration of silica fume SiO2 particles.
[0005] To achieve the above object, the present invention adopts the following technical solution:
[0006] In a first aspect, the present invention provides a silicon-based compacting agent, comprising modified silica fume, silicon dioxide, a high molecular polymer and fly ash, wherein the modifier used in the modified silica fume is selected from the general formula (R1): m Si(OR2) 4-m The organosilicon compound shown, wherein 0≤m≤3, R1 is selected from alkyl, cycloalkyl, aryl, halogenated alkyl, amine, halogen and hydrogen atom, and R2 is selected from alkyl, cycloalkyl, aryl, halogenated alkyl and amine.
[0007] The present invention uses an organosilicon compound containing siloxy groups to modify silica ash, attaches a large number of silanol groups to the surface of the silica ash, weakens the polarity between micro-nano particles, thereby improving the dispersibility of the silica ash, reducing agglomeration, and giving full play to the filling effect and volcanic ash effect of the silica ash.
[0008] According to some embodiments of the present invention, the organosilicon compound is selected from trimethylmethoxysilane, trimethylethoxysilane, trimethylphenoxysilane, tri-n-propylmethoxysilane, dimethyldimethoxysilane, dipropyldimethoxysilane, dibutyldimethoxysilane, dipentyldimethoxysilane, diisopropyldimethoxysilane, diisobutyldimethoxysilane, dimethyldiethoxysilane, cyclohexylmethyldiethoxysilane, cyclohexylmethyldimethoxysilane, cyclohexyldimethylmethoxysilane, hexyldiethylmethoxysilane, dicyclopentyldimethoxysilane, cyclopentyldiethylmethoxysilane, cyclopentylisopropyldimethoxysilane , cyclopentyl isobutyl dimethoxy silane, 4-methylcyclohexyl methyl dimethoxy silane, 4-methylcyclohexyl ethyl dimethoxy silane, 4-methylcyclohexyl propyl dimethoxy silane, di (4-methylcyclohexyl) dimethoxy silane, 4-methylcyclohexyl pentyl dimethoxy silane, 4-methylcyclohexyl cyclopentyl dimethoxy silane, octyl triethoxy silane, isooctyl triethoxy silane, diphenyl dimethoxy silane, diphenyl diethoxy silane, phenyl triethoxy silane, phenyl trimethoxy silane, vinyl trimethoxy silane, tetramethoxy silane, tetraethoxy silane, tetrapropoxy silane, tetrabutoxy silane and other organosilicon compounds. These organosilicon compounds can be used alone or in combination of two or more. The organosilicon compound of the present invention is preferably octyl triethoxy silane and isooctyl triethoxy silane.
[0009] According to some embodiments of the present invention, the modified silica fume is prepared by the following method:
[0010] The modified silica fume is obtained by immersing the silica fume in a reagent containing the above-mentioned organosilicon compound, heating and heat preservation, filtering and drying.
[0011] Preferably, the heating temperature is 60-70° C., and the insulation time is 1-2 hours.
[0012] The present invention uses modified silica fume in combination with nano silicon dioxide to exert the nucleation effect of nano crystals, promote cement hydration to generate more hydration products, exert volcanic ash reaction in the early stage of hydration, and promote the generation of high-density hydrated calcium silicate gel.
[0013] The addition of fly ash in the present invention can play a filling effect, a grading effect and a later pozzolanic effect in the cement paste, which is beneficial to refine the pore structure of the later cement paste, improve the microstructure, and enhance the mechanical strength and durability.
[0014] The high molecular polymer in the present invention can block the capillary channels inside the cement paste, reduce the flow of capillary water, and improve the compactness of the cement paste.
[0015] According to some embodiments of the present invention, the weight ratio of the modified silica fume to silicon dioxide is (3-30):1, preferably (3-10):1, for example 3:1, 3.5:1, 4:1, 4.5:1, 5:1, 5.5:1, 6:1, 6.5:1, 7:1, 7.5:1, 8:1, 8.5:1, 9:1, 9.5:1 or 10:1.
[0016] According to some embodiments of the present invention, the weight ratio of the modified silica fume to the high molecular polymer is (0.3-5):1, preferably (0.3-3.5):1, for example, 0.3:1, 0.5:1, 0.8:1, 1:1, 1.2:1, 1.5:1, 1.8:1, 2:1, 2.5:1, 2.8:1, 3:1, 3.2:1 or 3.5:1.
[0017] According to some embodiments of the present invention, the weight ratio of the modified silica fume to fly ash is (0.3-2):1, for example, 0.3:1, 0.5:1, 0.8:1, 1:1, 1.2:1, 1.5:1, 1.8:1 or 2:1.
[0018] According to some embodiments of the present invention, the densifier further comprises one or both of a water reducing agent and a defoaming agent.
[0019] According to some embodiments of the present invention, the compacting agent includes modified silica fume, silicon dioxide, a high molecular polymer, fly ash, a water reducing agent and a defoaming agent.
[0020] Preferably, the compacting agent includes, by weight: 50-150 parts of modified silica fume, 5-15 parts of silicon dioxide, 50-150 parts of high molecular polymer, 50-150 parts of fly ash, 1-2 parts of defoaming agent, and 2-4 parts of water reducing agent.
[0021] Preferably, the compacting agent comprises, by weight: 30-100 parts of modified silica fume, 10-15 parts of silicon dioxide, 30-100 parts of high molecular polymer, 50-100 parts of fly ash, 1-2 parts of defoaming agent and 2-4 parts of water reducing agent.
[0022] According to some embodiments of the present invention, the average particle size of the modified silica fume is 200 nm to 500 nm.
[0023] According to some embodiments of the present invention, the average particle size of the silicon dioxide is 10 nm to 50 nm.
[0024] According to some embodiments of the present invention, the high molecular polymer is selected from styrene-butadiene polymer, styrene-acrylic polymer and ethylene-vinyl acetate copolymer.
[0025] Preferably, the average molecular weight of the high molecular weight polymer is 100,000 to 1,000,000.
[0026] According to some embodiments of the present invention, the fly ash is ultrafine low-calcium fly ash. Preferably, the average particle size of the fly ash is not higher than 10 μm. Preferably, the CaO content in the fly ash is not higher than 10 wt%.
[0027] According to some embodiments of the present invention, the defoaming agent is selected from one or more of mineral oil defoaming agents, polyether defoaming agents and polyether-modified siloxane defoaming agents.
[0028] According to some embodiments of the present invention, the water reducer is selected from one or more of a naphthalene-based water reducer and a polycarboxylate water reducer. Preferably, the polycarboxylate water reducer is a polyether polycarboxylate super-efficient water reducer.
[0029] In a second aspect, the present invention provides a method for preparing a silicon-based compacting agent, comprising the following steps:
[0030] The modified silica fume, silicon dioxide and water reducing agent in the compacting agent described in the first aspect of the present invention are mixed and then mixed with water to obtain a mixed liquid;
[0031] The mixed liquid is mixed with the high molecular polymer, fly ash, optional defoaming agent and optional water reducing agent in the compacting agent described in the first aspect of the present invention to obtain the silicon-based compacting agent.
[0032] In a third aspect, the present invention provides use of the compacting agent described in the first aspect or the compacting agent obtained by the preparation method described in the second aspect in cement.
[0033] The cement of the present invention includes but is not limited to silicate cement, aluminate cement, sulphoaluminate cement, ferroaluminate cement, fluoroaluminate cement and phosphate cement.
[0034] Compared with the prior art, the present invention has the following beneficial effects:
[0035] (1) The present invention obtains modified silica fume with better dispersibility and hydrophobic effect by modifying ordinary silica fume, thereby improving the dispersibility of silica fume in cement paste, increasing the uniformity and refined pore size of cement paste materials, and increasing the degree of polymerization of hydrated calcium silicate gel.
[0036] (2) The present invention promotes cement hydration reaction to generate more hydration products and improves the activity of volcanic ash by adding nano-silicon dioxide based on the microcrystalline nucleation principle, thereby further refining the pore structure of the cement matrix.
[0037] (3) The high molecular weight polymer selected in the present invention can block the capillary channels inside the cement paste, reduce the flow of capillary water, and improve the compactness of the cement paste. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 1 is a flow chart of the preparation process of the compacting agent in an embodiment of the present invention.
[0039] Figure 2 This is the particle size distribution diagram of silica fume before and after modification.
[0040] Figure 3 The pore volume distribution diagram of cement paste without densifier and cement paste with densifier in Examples 1-3 is shown.
[0041] Figure 4 Figure 2 is a scanning electron microscope image of cement paste before and after the addition of the densifier, wherein Figure a is a scanning electron microscope image of cement paste added with the densifier of comparative example 1 and cured for 28 days, Figure b is a scanning electron microscope image of cement paste added with the densifier of comparative example 2 and cured for 28 days, Figure c is a scanning electron microscope image of cement paste added with the densifier of example 3 and cured for 28 days, and Figure d is a scanning electron microscope image of cement paste without the addition of the densifier and cured for 28 days. DETAILED DESCRIPTION
[0042] In order to better illustrate the present invention and facilitate understanding of the technical solution of the present invention, the technical solution of the present invention will be described in detail below through embodiments.
[0043] Reagents used in the following examples:
[0044] The average particle size of nano-silicon dioxide is 20nm;
[0045] The high molecular weight polymer is styrene-butadiene polymer with an average molecular weight of 600,000;
[0046] The average particle size of ultrafine low-calcium fly ash is 10 μm;
[0047] The defoamer is 2111 type defoamer produced by Shanghai BASF New Materials Co., Ltd.;
[0048] The polycarboxylate water reducer is a polyether polycarboxylate super-efficient water reducer purchased from Beijing Zhongsiheju New Materials Co., Ltd.
[0049] The modified silica fume is a hydrophobic silica fume made in the laboratory. The specific preparation method is as follows:
[0050] Immerse ordinary silica fume in ZG-S70 silane emulsion (purchased from Beijing Zhongsi Heju New Materials Co., Ltd., with an active ingredient of 47% octyltriethoxysilane), heat to 60-70°C, stir and keep warm for 1-2 hours, filter and dry the silica fume in a 105°C oven for 24 hours until constant weight. The particle size distribution of silica fume particles before and after modification is as follows: Figure 2 As shown in the figure, it can be seen that the average particle size of modified silica fume is 200nm~500nm, which is smaller than the average particle size of ordinary silica fume.
[0051] The preparation process of the silicon-based compacting agent described in the following examples and comparative examples is as follows: Figure 1 As shown, the specific method is as follows:
[0052] (1) Modified silica fume, nano silicon dioxide and polycarboxylic acid water reducer are mixed in proportion to obtain a dry powder mixture; the dry powder mixture is mixed with deionized water in a ratio of 1:100 to prepare a solution, ultrasonically dispersed for 15 to 30 minutes, and then cooled to room temperature.
[0053] (2) The mixed solution is mixed with butadiene-styrene polymer, ultrafine low-calcium fly ash and 2111 type defoaming agent to obtain a silicon-based compacting agent.
[0054] Example 1
[0055] A compacting agent, comprising the following components in parts by mass:
[0056] 50 parts of modified silica fume, 5 parts of nano silicon dioxide, 50 parts of styrene-butadiene polymer, 50 parts of ultrafine low-calcium fly ash, 1 part of defoamer, and 2 parts of polycarboxylic acid water reducer.
[0057] Example 2
[0058] A compacting agent, comprising the following components in parts by mass:
[0059] 100 parts of modified silica fume, 10 parts of nano silicon dioxide, 100 parts of styrene-butadiene polymer, 50 parts of ultrafine low-calcium fly ash, 2 parts of defoamer, and 3 parts of polycarboxylic acid water reducer.
[0060] Example 3
[0061] A compacting agent, comprising the following components in parts by mass:
[0062] 100 parts of modified silica fume, 10 parts of nano silicon dioxide, 100 parts of styrene-butadiene polymer, 100 parts of ultrafine low-calcium fly ash, 2 parts of defoamer, and 4 parts of polycarboxylic acid water reducer.
[0063] The specific composition (mass fraction) of the densifier of Examples 1-13 is shown in Table 1.
[0064] Table 1
[0065]
[0066] Comparative Example 1
[0067] A compacting agent, comprising the following components in parts by mass:
[0068] 100 parts of modified silica fume, 100 parts of styrene-butadiene polymer, 100 parts of ultrafine low-calcium fly ash, 2 parts of defoamer, and 4 parts of polycarboxylic acid water reducer.
[0069] Comparative Example 2
[0070] A compacting agent, comprising the following components in parts by mass:
[0071] 100 parts of silica fume (unmodified), 10 parts of nano silicon dioxide, 100 parts of styrene-butadiene polymer, 100 parts of ultrafine low-calcium fly ash, 2 parts of defoamer, and 4 parts of polycarboxylic acid water reducer.
[0072] Performance Testing
[0073] Pour the silicon-based densifier prepared in Examples 1-13 and Comparative Examples 1-2 into a mortar mixer, replace a part of 1000 parts of cement with equal mass, add water according to a water-cement ratio of 0.35 for stirring, and add a water reducer to adjust the fluidity, first stir slowly for 1 to 2 minutes, then stir quickly for 2 to 4 minutes, and then pour the evenly stirred cement slurry into a mold, vibrate into shape, remove the mold and place it in a standard curing room until the age.
[0074] A reference sample (cement without densifier) was set up, and the pore volume, average pore size and calcium-silicon ratio Ca / Si of the reference sample and the cement added with the silicon-based densifier provided in Examples 1-13 and Comparative Examples 1-2 at 56 days of age were tested. The results are shown in Table 2.
[0075] The pore volume distribution diagram of the cement added with the silicon-based compacting agent provided in Examples 1-3 at 56 days of age is as follows: Figure 3 shown.
[0076] Table 2 and Figure 3 The test methods for cement pore volume and average pore size are as follows:
[0077] The test blocks cured to the age were cored and cut into cylinders, immersed in isopropanol for 24 to 48 hours to terminate hydration, then placed in a vacuum drying oven at 40°C for 24 to 48 hours to constant weight, and tested and analyzed using an AUTOSACN-33 mercury intrusion porosimeter.
[0078] In Table 2, the calcium-silicon ratio Ca / Si test method of hydrated calcium silicate gel in cement paste is as follows:
[0079] The core of the sample cured to the age was cut into slices with smooth upper and lower surfaces, and the hydration was terminated in the same way and then vacuum dried and then sprayed with gold. The Phenom electron microscope energy spectrum integrated machine was used to observe the microscopic morphology of the sample, detect the elemental composition of the hydration product, and determine the calcium-silicon ratio of the hydrated calcium silicate gel.
[0080] Table 2
[0081]
[0082]
[0083] The content of gel pores (<10nm) is proportional to the content of hydrated calcium silicate gel in the hardened cement paste. Increasing the content of gel pores is beneficial to making the matrix more compact. Transition pores (10-100nm) are small-diameter capillary pores. Reducing the content of transition pores is beneficial to refining the pore structure.
[0084] It can be seen from Table 2 that: with the increase of modified silica fume dosage, the gel pore content continues to increase, but if the silica fume dosage is too high, the transition pore volume will also increase; adding nano-SiO2 can increase the gel pore content while reducing the transition pore volume and the average pore size; adding ultrafine low-calcium fly ash can increase the gel pore content and slightly increase the transition pore volume; adding modified silica fume, nano-SiO2, and fly ash at the same time can play a synergistic role, especially Example 2, Example 3, Example 6, Example 7, Example 10 and Example 12 can significantly increase the gel pore volume while significantly reducing the transition pore volume, which is more conducive to the compaction of the matrix. Compared with Comparative Example 1, the addition of nano-SiO2 in Examples 1-13 can further increase the gel pore content and reduce the transition pore content; compared with Comparative Example 2 (adding ordinary silica fume), the addition of modified silica fume in Examples 1-13 significantly increases the gel pore volume, indicating that modified silica fume is more conducive to the formation of hydrated calcium silicate gel, refines the pore size, and makes the hardened cement slurry structure more compact.
[0085] The microstructures of the cement paste mixed with comparative example 1, comparative example 2, and embodiment 3 and cured for 28 days and the reference sample were tested by electron scanning electron microscopy (see Figure 4 The results show that the modified silica fume has fewer agglomerates in the cement slurry, indicating that it has good dispersibility in the cement slurry, and the calcium silicate hydrate gel is smoother and denser when added with the densifier of Example 3, indicating that the silicon-based densifier is conducive to the densification of the calcium silicate hydrate gel.
[0086] The above description uses specific examples to illustrate the present invention, but is not intended to limit the present invention. For those skilled in the art, simple deduction, deformation or replacement can be proposed through creative work based on the concept of the present invention. The protection scope of the present invention shall be based on the protection scope defined in the claims.
Claims
1. A silicon-based compacting agent, which comprises, by weight: 30-100 parts of modified silica fume, 10-15 parts of silicon dioxide, 30-100 parts of high molecular polymer, 50-100 parts of fly ash, 1-2 parts of defoamer and 2-4 parts of water reducing agent; The modified silica fume modifier is selected from organic silicon compounds, and the organic silicon compound is selected from at least one of the following compounds: trimethylmethoxysilane, trimethylethoxysilane, trimethylphenoxysilane, tri-n-propylmethoxysilane, dimethyldimethoxysilane, dipropyldimethoxysilane, dibutyldimethoxysilane, dipentyldimethoxysilane, diisopropyldimethoxysilane, diisobutyldimethoxysilane, dimethyldiethoxysilane, cyclohexylmethyldiethoxysilane, cyclohexylmethyldimethoxysilane, cyclohexyldimethylmethoxysilane, hexyldiethylmethoxysilane, dicyclopentyldimethoxysilane, cyclopentyldiethylmethoxysilane Silanes, cyclopentylisopropyldimethoxysilane, cyclopentylisobutyldimethoxysilane, 4-methylcyclohexylmethyldimethoxysilane, 4-methylcyclohexylethyldimethoxysilane, 4-methylcyclohexylpropyldimethoxysilane, di(4-methylcyclohexyl)dimethoxysilane, 4-methylcyclohexylpentyldimethoxysilane, 4-methylcyclohexylcyclopentyldimethoxysilane, octyltriethoxysilane, isooctyltriethoxysilane, diphenyldimethoxysilane, diphenyldiethoxysilane, phenyltriethoxysilane, phenyltrimethoxysilane, vinyltrimethoxysilane, tetramethoxysilane, tetraethoxysilane, tetrapropoxysilane, tetrabutoxysilane; The high molecular polymer is selected from styrene-butadiene polymer, styrene-propylene polymer and ethylene-vinyl acetate copolymer; The defoamer is selected from one or more of mineral oil defoamers, polyether defoamers and polyether-modified siloxane defoamers; The water reducer is selected from one or more of naphthalene-based water reducers and polycarboxylic acid water reducers.
2. The compacting agent according to claim 1, characterized in that The organosilicon compound is selected from octyltriethoxysilane and / or isooctyltriethoxysilane.
3. The compacting agent according to claim 1 or 2, characterized in that: The modified silica fume is prepared by the following method: The silicon ash is immersed in a reagent containing the organosilicon compound, heated, filtered and then dried to obtain the modified silicon ash.
4. The compacting agent according to claim 3, characterized in that The heating temperature is 60-70° C., and the insulation time is 1-2 hours.
5. The compacting agent according to any one of claims 1 to 2, characterized in that The weight ratio of the modified silica fume to silicon dioxide is (3-10):
1.
6. The compacting agent according to any one of claims 1 to 2, characterized in that The average particle size of the modified silica fume is 200 nm to 500 nm; and / or the average particle size of the silicon dioxide is 10 nm to 50 nm.
7. The compacting agent according to any one of claims 1 to 2, characterized in that The average molecular weight of the high molecular weight polymer is 100000-1000000; And / or the CaO content in the fly ash is not higher than 10wt%.
8. The compacting agent according to any one of claims 1 to 2, characterized in that The defoamer is a 2111 type defoamer; And / or the polycarboxylate water reducer is a polyether polycarboxylate super efficient water reducer.
9. The compacting agent according to claim 7, characterized in that: The average particle size of the fly ash is not higher than 10 μm.
10. The method for preparing the silicon-based compacting agent according to any one of claims 1 to 9, comprising the following steps: The modified silica fume, silicon dioxide and a water reducing agent are mixed and then mixed with water to obtain a mixed liquid; The mixed liquid is mixed with the high molecular polymer, fly ash and defoamer to obtain a silicon-based compacting agent.
11. Use of the compacting agent according to any one of claims 1 to 9 or the compacting agent obtained by the preparation method according to claim 10 in cement.
12. The use according to claim 11, characterized in that: The cement includes one or more of silicate cement, aluminate cement, sulphoaluminate cement, ferroaluminate cement, fluoroaluminate cement and phosphate cement.
Citation Information
Patent Citations
Composite compacting agent
CN110451840A
Preparation method and application of modified silica fume material
CN112939499A